The Role of the Seating Element in Social Status - Söğüt, Mahmut Atilla (Journal of Interior Design and Academy, 2024)
Seating furniture, an indispensable part and necessity of a space, has evolved in design throughout history as lifestyles, expectations, and aesthetic preferences of people have changed. The designs of seating furniture have adapted to this evolution, reflecting users' differences as a reflection of societal diversity and acceptance. This subject is important both in terms of the observed role of seating furniture and in determining the position of individuals in their social interactions. Seating furniture, like a mirror, reflects the social statuses, preferences, cultural backgrounds, and even emotional states of individuals. From traditional designs to modern and contemporary ones, seating furniture is one of the significant and defining elements in a space for determining status and personalization. Throughout the known history of furniture, seating furniture has stood out as a status-defining piece of furniture, supporting the user's status and personalization. This article investigates the pursuit of individual status and personalized furniture through seating furniture.